2011
DOI: 10.1111/j.1365-2966.2011.19812.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon deficiencies in the primaries of some classical Algols★

Abstract: The equivalent widths (EWs) of the C iiλ4267 Å line were measured for the mass‐gaining primary stars of 18 Algol‐type binary systems. The EWs of the gainers were compared with the EWs of single standard stars that have the same effective temperature and luminosity class. This comparison clearly indicates that the EWs of the gainers are systematically smaller than those of the standard stars. The primary components of the classical Algols, located in the main‐sequence band of the Hertzsprung–Russell diagram, ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Since the transferred material from the evolved donor star is C poor, when this is mixed with the original matter of the gainer the C amount appears to decrease (de Greve & Sarna 1997). Thus, Ibanoglu et al (2012) found a correlation between the EWs of the C II 4267 Å line and the mass transfer rate. As the mass transfer rate increases, the EW of C II 4267 Å decreases.…”
Section: Accretion Discmentioning
confidence: 94%
See 1 more Smart Citation
“…Since the transferred material from the evolved donor star is C poor, when this is mixed with the original matter of the gainer the C amount appears to decrease (de Greve & Sarna 1997). Thus, Ibanoglu et al (2012) found a correlation between the EWs of the C II 4267 Å line and the mass transfer rate. As the mass transfer rate increases, the EW of C II 4267 Å decreases.…”
Section: Accretion Discmentioning
confidence: 94%
“…Using the correlation EW s/Ṁ for the Algols studied by Ibanoglu et al (2012) we measured a mean value of the EW/λ of −4.7 ± 0.3 and thus we estimate a mass transfer rate aroundṀ = −5 × 10 −8 M /yr. This mass transfer rate is lower than the value predicted from the evolutionary analysis of DQ Vel with the gainer star in synchronous rotation (see Sect.…”
Section: Ibanoglumentioning
confidence: 99%
“…In a period analysis of ten semi-detached Algol-type binaries, Ibanoǧlu et al (2012) found u Her to be the system with the small- est period changes. We used their ephemeris 3 during our analysis; Tprim.min.…”
Section: Light Curve Modellingmentioning
confidence: 99%
“…In that case, the surface carbon abundance of the gainer cannot be lower than that of the donor star, however. Multiple authors have used the sketched scenario to explain the surface abundance anomalies observed in several other Algol-type stars; these include Ibanoǧlu et al (2012) for GT Cep, AU Mon, and TU Mon, Kolbas et al (2014) for u Her, and Dervişoglu et al (2018) for δ Lib.…”
Section: Discussionmentioning
confidence: 99%